Development of a health knowledge test for U.P. High School students - Mejillano, Evelina A. 1937- (s.n.], 1968)
This paper presents an instrument which will measure the extent of the health knowledge of high school students at the University of the Philippines. The techniques involved in test construction were also developed in the study.